2001
DOI: 10.1016/s0370-2693(01)00887-5
|View full text |Cite
|
Sign up to set email alerts
|

Probing the 6He halo structure with elastic and inelastic proton scattering

Abstract: Proton elastic scattering and inelastic scattering to the first excited state of 6 He have been measured over a wide angular range using a 40.9A MeV 6 He beam. The data have been analyzed with a fully microscopic model of proton-nucleus scattering using 6 He wave functions generated from large space shell model calculations. The inelastic scattering data show a remarkable sensitivity to the halo structure of 6 He. PACS number(s): 25.40.Cm, 25.40.Ep, 24.10.Ht Typeset using REVT E X * present address:INFN-La… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
68
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 38 publications
6
68
1
Order By: Relevance
“…Nowadays, a substantial amount of experimental data exists for the cross sections of 6 He+p elastic scattering at different energies. For example, proton elastic scattering angular distributions were measured at incident energies less than 100 MeV/N for 6 He, namely 25.2 [1,2,3,4], 38.3 [5], 41.6 [6,7,8], and 71 MeV/N [9,10] and at energy of 700 MeV/N for He and Li isotopes (e.g. refs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, a substantial amount of experimental data exists for the cross sections of 6 He+p elastic scattering at different energies. For example, proton elastic scattering angular distributions were measured at incident energies less than 100 MeV/N for 6 He, namely 25.2 [1,2,3,4], 38.3 [5], 41.6 [6,7,8], and 71 MeV/N [9,10] and at energy of 700 MeV/N for He and Li isotopes (e.g. refs.…”
Section: Introductionmentioning
confidence: 99%
“…In [21] a comparison of the obtained results has been performed to those from the alpha-core approach with the complex and fully non-local effective interaction [22] and also with the non-core model based on the large-scale shell-model (LSSM) calculations (refs. [7,36,37] and references therein). It was shown that the elastic scattering is a good tool to distinguish between different density distributions [21].…”
Section: Introductionmentioning
confidence: 99%
“…For example for energies well above E proj. = 10 MeV/u, the microscopic approach of the Jeukenne, Lejeune, and Mahaux (JLM) potential was the basis for several such studies [1][2][3][4][5][6][7][8][9]. This potential was derived by Jeukenne-Lejeune-Mahaux [10] and applied in Refs.…”
mentioning
confidence: 99%
“…In order to explore its structure and spectroscopy we measured (p,p') reaction. It is a powerful probe to investigate the ground state (gs) and transition densities to excited states of the light exotic nuclei, as shown by the recent results obtained on the halo of 6 He [1]. Previous 8 He(p,p') data exist; the (p,p') was measured at RIKEN [7] and a 2 + resonance was observed at 3.57±0.12 MeV (width Γ = 0.5 ± 0.35 MeV).…”
Section: Introductionmentioning
confidence: 99%
“…Previous 8 He(p,p') data exist; the (p,p') was measured at RIKEN [7] and a 2 + resonance was observed at 3.57±0.12 MeV (width Γ = 0.5 ± 0.35 MeV). But the low statistics and reduced angular range for the (p,p') distributions did not allow to perform a detailed microscopic analysis of the density profiles, as done for 6 He in [1].…”
Section: Introductionmentioning
confidence: 99%